Meta-analysis of ciltacabtagene autoleucel versus physician's choice therapy for the treatment of patients with relapsed or refractory multiple myeloma. (3rd October 2022) - Costa, Luciano J.; Hari, Parameswaran; Berdeja, Jesus G.; De Stefano, Valerio; Gay, Francesca; Hooper, Becky; Bartlett, Meaghan; Haltner, Anja; Rosta, Emily; Kumar, Shaji; Martin, Thomas; Mateos, Maria-Victoria; et al.
Abstract: Objective: In the absence of head-to-head trials, indirect treatment comparisons (ITCs) between ciltacabtagene autoleucel (cilta-cel; in CARTITUDE-1) and treatments used in real-world clinical practice (physician's choice of treatment [PCT]), were previously conducted. We conducted multiple meta-analyses using available ITC data to consolidate the effectiveness of cilta-cel versus PCT for patients with triple-class exposed relapsed or refractory multiple myeloma (RRMM). Methods: Five ITCs were assessed for similarity to ensure robust comparisons using meta-analysis. Effectiveness outcomes were overall survival (OS), progression-free survival (PFS), time to next treatment (TTNT), and overall response rate (ORR). A robust variance estimator was used to account for the use of CARTITUDE-1 in each pairwise ITC. Analyses were conducted in both treated and enrolled populations of CARTITUDE-1. Results: Four ITCs were combined for evaluation of OS. Results were statistically significantly in favor of cilta-cel versus PCT in treated patients (hazard ratio [HR]: 0.24, 95% confidence interval [CI]: 0.22–0.26). Three ITCs were combined for evaluation of PFS and TTNT. Cilta-cel reduced the risk of progression and receiving a subsequent treatment by 80% (HR: 0.20 [95% CI: 0.06, 0.70]) and 83% (HR: 0.17 [95% CI: 0.12, 0.26]), respectively. Three ITCs were combined for evaluation of ORR. Cilta-cel increased the odds of achieving an overall response by 86-times versus PCT in treated patients. Findings were consistent in the enrolled populations and across sensitivity analyses. Conclusions: Evaluating multiple indirect comparisons, cilta-cel demonstrated a significantly superior advantage over PCT, highlighting its effectiveness as a therapy in patients with triple-class exposed RRMM.